T-Hardy Rogers Contraction and Fixed Point Results in Cone Metric Spaces with c-Distance - Surendra Kumar Tiwari; Kaushik Das (International Journal of Mathematics And its Applications, 2017)
In this paper, we introduce the T-Hardy-Rogers's contraction under the concept of c-distance in cone metric spaces and prove the existence and uniqueness fixed point results. The presented theorem extends and generalizes several well known comparable results in literature.